ax+5=bx-cforx

Simple and best practice solution for ax+5=bx-cforx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ax+5=bx-cforx equation:


Simplifying
ax + 5 = bx + -1cforx

Reorder the terms:
5 + ax = bx + -1cforx

Solving
5 + ax = bx + -1cforx

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + ax = bx + -5 + -1cforx

Combine like terms: 5 + -5 = 0
0 + ax = bx + -5 + -1cforx
ax = bx + -5 + -1cforx

Reorder the terms:
ax = -5 + bx + -1cforx

Divide each side by 'x'.
a = -5x-1 + b + -1cfor

Simplifying
a = -5x-1 + b + -1cfor

Reorder the terms:
a = b + -1cfor + -5x-1

See similar equations:

| 8*4*k+9*5=(5-3)m | | 1-12+14= | | 15x-21=8x+28 | | 4x-x+2=5 | | 28=3x-84 | | 48=-6x+18 | | 8-27=3y-2 | | (3d+8)+(4m+1)= | | 2/7+7m/3=62/21 | | 10-3c=10+9c | | 1x+7=2x+3 | | 6+(5+8)*4= | | 3x-4-x=6x-12 | | 6x-29=5x-7 | | 15x-8x=40+9 | | 5p^2-6=7p | | -10-3c=10+9c | | 6x+4=8x-7(-x+3)-4x | | -11x+43=-34 | | 2x^67=9r | | 12-x=-32 | | 22-5r=2r | | x^2+x=4.27 | | 6p+5=17 | | 2(x^2-7x+21)=0 | | 502.4=3.14(4)h | | Y-x=-9 | | 30+x=167 | | .5(2n-3)-.1=.4(6+2n) | | 5*8+6y=94 | | 15-8x=49 | | 8q-q=14 |

Equations solver categories